(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
This contribution explores the different semantic trajectories of the root mun- in Latin and Etruscan in order to deepen understanding of women’s “insignia” in Roman and Etruscan society. Regarding Latin women, munditia may represent an example of moral ‘insignia.’ In Etruria, the appearance of the word munθuχ on a mirror, as the name of a female figure tasked with the maintenance of physical, natural and spiritual order, may indicate the feminine use of mirrors in catoptromancy and the concrete significance of the root mun- in Etruscan.